ASSESSMENT OF THE ANATOMICAL AND FUNCTIONAL EFFECTIVENESS OF THE MANCHESTER OPERATION IN PELVIC ORGAN PROLAPSE - Najmutdinova Dilbar; Ismailova Mashkura (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Pelvic organ prolapse is one of the most common gynecological pathologies among women and is characterized by the downward displacement of pelvic organs due to weakening of the pelvic floor muscular and ligamentous apparatus. This pathology leads to urinary and bowel dysfunction, decreased sexual activity, chronic discomfort, and deterioration in quality of life. In recent years, there has been growing interest in organ-preserving surgical methods aimed at maintaining reproductive function, particularly the Manchester operation.This study evaluated the anatomical and functional effectiveness of the Manchester operation in pelvic organ prolapse. During the research, the degree of prolapse according to the POP-Q system, cervical length, condition of the vaginal walls, hiatal area parameters, and anatomical changes of the pelvic floor were assessed before and after surgery. In addition, changes in patients’ quality of life, sexual activity, urinary, and bowel functions were evaluated using functional criteria.The results demonstrated that the Manchester operation is highly effective in restoring the anatomical position of pelvic organs, reducing prolapse symptoms, strengthening pelvic floor support structures, and improving patients’ quality of life. The postoperative period was characterized by a low recurrence rate of prolapse and stable functional outcomes.The obtained results indicate that the Manchester operation is one of the effective organ-preserving surgical methods for the treatment of pelvic organ prolapse and provides a scientific basis for improving clinical approaches to its application.